Test the Moderating and Mediating role of organizational culture in the relationship between servant leadership and employees performance (an analytical research of the views of a sample of employees in Al Zawraa general company) - Mustafa Hatwan Rhima; Mohammed Abd Ahmed (Journal of Techniques)
This research aims to study the expected role of organizational culture between the servant leadership in its dimensions (support and support of employees, forgiveness, and originality) and the performance of workers in whether it is a moderating role that modifies the strength and direction of the relationship between the independent variable and the dependent variable or just a mechanism to transfer the effect of the independent variable on the dependent variable this is called the mediating role. The targeted research sample was represented by the employees working in Al-Zawraa Public Company and the research sample reached (76) individuals of different job levels. For the purpose of collecting data for conducting statistical analyzes, the research relied on the questionnaire as a main tool, as (100) questionnaires were distributed to the employees of Al Zawraa Public Company, Al-Mansour site, Gas Department Medical and industrial. The number of retrieved questionnaires was (79), and valid for statistical analysis was (76). The data were analyzed using (AMOS) version 23 program. To achieve the research objectives, many statistical methods were used, represented by (the arithmetic mean, standard deviation, coefficient of variation, Pearson correlation coefficient and multiple linear regression). This research reached a set of conclusions, perhaps the most important of which is inferring the fact that organizational culture plays an interactive role and an intermediate role in the relationship between servant leadership and the performance of employees.